An AKTIVITAS ANTIOKSIDAN DAN FOTOPROTEKSI DARI EKSTRAK SERTA FRAKSI DAUN JARUM TUJUH BILAH (Pereskia bleo (Kunth)D.C) - Irma Erika Herawati; Ginayanti Hadisoebroto; Ita Inayah; Lisna Dewi; Syulastri Effendi; Syumillah Saepudin (Fakultas Farmasi Universitas Buana Perjuangan Karawang, 2025)
Pereskia bleo (Kunth) D.C, commonly known as “jarum tujuh bilah,” is a plant widely found in Indonesia with elliptic to oblong-shaped leaves. This plant is traditionally recognized for its therapeutic properties, including treatments for rheumatism, inflammation, gastric disorders, ulcers, diabetes, hypertension, and as a body revitalizer. The leaves of this plant are known to contain various secondary metabolites, such as alkaloids, tannins, saponins, flavonoids, steroids, and phenolic compounds. These constituents exhibit antioxidant activity and the ability to absorb ultraviolet radiation, indicating potential as a natural sunscreen agent. This study aims to evaluate the antioxidant and photoprotective activities of the extract and fractions of P. bleo leaves through in vitro assays using UV-Vis spectrophotometry. Extraction was conducted via maceration using 70% ethanol as the solvent, followed by liquid–liquid fractionation with solvents of varying polarities: distilled water, n-hexane, and ethyl acetate. The results demonstrated that the ethanolic extract exhibited strong antioxidant activity with an IC₅₀ value of 41.5 ppm and an antioxidant activity index (AAI) of 0.963. The highest photoprotective activity was observed in the ethyl acetate fraction, with an SPF value of 73.229 (categorized as ultra protection) and an erythema transmission percentage of 0.034797 (indicative of effective sunblock activity)